"KONSENSUM” TUSHUNCHASINING O'ZLASHTIRISHI YUZASIDAN OLIB BORILGAN TADQIQOT VA UNING NATIJALARI - Qodirova Munisabonu Ibrohimjon qizi, (TADQIQOTLAR, 2025)
Abstract: This article presents the research conducted on the assimilation of the concept consensus into the Uzbek language and discusses its key findings. The study examines the linguistic, semantic, and cultural aspects of the concept, identifies its Uzbek equivalents, and analyzes its functional features and usage contexts in Uzbek discourse.  Surveys  conducted  among  respondents  helped  determine  the  perception, comprehension,  and  frequency  of  use  of  the  concept  “consensus”  in  the  Uzbek language. The findings contribute  to developing recommendations for the effective integration of this concept into Uzbek and its appropriate use in both scientific and social discourse.